Nuclear safety a human factors perspective - Misumi, Jūji 1924-; Wilpert, Bernhard 1936-; Miller, Rainer (Taylor & Francis, 1999)
For many years, as a direct result of international governmental concern, the nuclear power industry has been at the forefront of industrial safety. This text represents a cross-disciplinary look at the human factors developments in this industry, with wider applications for the entire industrial sector. Technical, psychological and social aspects of industrial safety come under the scrutiny of scientists and engineers from an array of different backgrounds. The contributors are international safety scientists from the USA, Japan and Europe, and their chapters deal with a variety of issues: from theoretical aspects of applicable cultural models, to reviews of actual safety performance in specific plants.